Slumberland a wellness retreat that specialized in treating people with insomnia - King, Harriet Andrea A.
Sleep is a central part of human life. Around one third of man's life is spent asleep in order to function well on the two thirds. Sleep determines how people act, how they function the following day, and their disposition, while wakefulness decides when people sleep, their quality of sleep, and how much time they spend sleeping. Sleep and wakefulness are more connected than most think. Although there is still plenty to be known of sleep, one thing that has been validated for years is the necessity of sleep to function in everyday life. Today's modern society can be described as a race competition towards the finish line. Work is fast paced, cutthroat, and nonstop. Since the invention of the lightbulb, the city has found the means to be open for twenty four hours, seven days a week. Stress is present in most aspects of life may it be from school, work, or family. A lifestyle that is full of stress, irregularity in schedule, and shifting of time frames introduces consequences in health. Two of which are the disruption of the human circadian clock, and psychological problems such as depression and anxiety. Both of these may lead to a different disorder; Insomnia, which is the difficulty to maintain or fall asleep. Insomnia is the most common sleep disorder; in fact, around 30% of adults have symptoms of Insomnia, while 10% have Insomnia that is severe enough to cause daytime consequences. This study aims to help people with Insomnia in their treatment through the use of the landscape. The healing power of the landscape is combined with the utilization of light, and the execution of a program of activities fitted to the individual to create a retreat facility that focuses on the treatment of people with Insomnia. Through these introduced elements, the facility becomes a potent landscape to restore the sleep that was lost from Insomnia. The output of visiting the landscape are guests who are either treated of their disorder, or are equipped with the knowledge, mindset, behavior; and habits to continue treatment at home.